Some Aspects of Syntactic Development in Marathi Speaking Children Aged 21/2-3 Years-A Descriptive Study - Gore, Madhuri S (Journal of All India Institute of Speech and Hearing)
Every human child acquires the language of his community, provided he is given a fighting chance by heredity and environment. Language is central to all communities of human beings, ’essential for the regulation of every community the instruction of its young the identification of its members ’ (Brown and Miller, 1980), Language is complex and involves highly abstract organizational principles, but child masters a linguistic system, that is for practical purposes identical to the one employed by those around him in a few years.